Utilising Utaut Model In Defining Influencing Factors Of Ubiquitous Technology (U-Tech) Usage - Sedek, Muliati; Ahmad, Rabiah; Mahmud, Rosnaini; Jamal, Azmalniza (Medwell Journals, 2017)
As according to the Unified Theory of Acceptance and Utilisation of Technology (UTAUT), Performance Expectancy (PE), Effort Expectancy (EE), Behavioural Intention (BI), Facilitating Conditions (FC) and Social Status (SS) have been identified as factors that influence the utilisation of technology. Thus, the focus of this study was to confirm whetherthe determined factors such as above contribute towards ubiquitous technology (u-tech) such as laptops, smartphones and tablets. The study also aims to develop a new model on the factors that influence the utilisation of u-tech as learning tools among students in the institutions of higher learning in Malaysia. This study was based on a quantitative research in which the structural equation modelling using AMOS was employed. The results attained from the analysis produced a reliable model towards u-tech usage. The significant paths found were TC influences u-tech usage (β = 0.35, p = 0.000) PE influences u-tech usage (β = 0.41, p = 0.000) and FC influences u-tech usage (β = 0.23, p = 0.000). Meanwhile, the structural paths for EE (β = 0.26, p = 0.000) and SS (β = 0.52, p = 0.000) towards u-tech usage were mediated by BI. Therefore, it can be concluded that, 63% of the variance in u-tech usage described by the five factors.